Analysis of Outer Membrane Vesicles Indicates That Glycerophospholipid Metabolism Contributes to Early Symbiosis Between Sinorhizobium fredii HH103 and Soybean - Dongzhi Li; Ziqi Li; Jing Wu; Zhide Tang; Fuli Xie; Dasong Chen; Hui Lin; Youguo Li (Molecular Plant-Microbe Interactions, 2022)
Gram-negative bacteria can produce outer membrane vesicles (OMVs), and most functional studies of OMVs have been focused on mammalian-bacterial interactions. However, research on the OMVs of rhizobia is still limited. In this work, we isolated and purified OMVs from Sinorhizobium fredii HH103 under free-living conditions that were set as control (C-OMVs) and symbiosis-mimicking conditions that were induced by genistein (G-OMVs). The soybean roots treated with G-OMVs displayed significant deformation of root hairs. G-OMVs significantly induced the expression of nodulation genes related to early symbiosis, while they inhibited that of the defense genes of soybean. Proteomics analysis identified a total of 93 differential proteins between C-OMVs and G-OMVs, which are mainly associated with ribosome synthesis, flagellar assembly, two-component system, ABC transporters, oxidative phosphorylation, nitrogen metabolism, quorum sensing, glycerophospholipid metabolism, and peptidoglycan biosynthesis. A total of 45 differential lipids were identified through lipidomics analysis. Correlation analysis of OMV proteome and lipidome data revealed that glycerophospholipid metabolism is the enriched Kyoto Encyclopedia of Genes and Genomes metabolic pathway, and the expression of phosphatidylserine decarboxylase was significantly up-regulated in G-OMVs. The changes in three lipids related to symbiosis in the glycerophospholipid metabolism pathway were verified by enzyme-linked immunosorbent assay. Our results indicate that glycerophospholipid metabolism contributes to rhizobia-soybean symbiosis via OMVs.[Graphic: see text] Copyright © 2022 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.